Heroism in the New Black Poetry : Introductions and Interviews - Melhem, D. H. (Book collections on Project MUSE., 2015)
D.H. Melhem's clear introductions and frank interviews provide insight into the contemporary social and political consciousness of six acclaimed poets: Amiri Baraka, Gwendolyn Brooks, Jayne Cortez, Haki R. Madhubuti, Dudley Randall, and Sonia Sanchez. Since the 1960s, the poet hero has characterized a significant segment of Black American poetry. The six poets interviewed here have participated in and shaped the vanguard of this movement. Their poetry reflects the critical alternatives of African American life -- separatism and integration, feminism and sexual identity, religion and spirituali.